New Media and Women’s Da’wah Movement in the Post Covid-19 Era - Ummah, Athik Hidayatul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Internet and social media are sources of information and religious knowledge references, especially for millennials and middle-class urban communities. The transformation of Islamic da’wah mode from offline to online is still dominated by men preachers. Actually, women's da’wah movement can be found in new media platforms but they get less attention. This study aims to explore the role of women preachers in Islamic da’wah in the digital era. Second, to explore the digital da’wah strategy of the Islamic Gender Justice studies (Ngaji KGI) community. The research method used to analyze the problem above was a qualitative-research with an anthropological-da’wah approach. This paper shows that the role of female da’i is equal and their position is crucially the same as that of male da’i. In addition, Ngaji GKI strategy by adhering to relative advantage, compatibility, complexity, triability and observability makes its existence different from other communities.